FORECASTING EVENTUAL OPERATIONAL PERFORMANCE OF THE SWH SYSTEM USING ANN APPROACH- SPECIAL REFERENCE TO BHOPAL (M.P.) - Saraf , Ritul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Solar radiation is an important parameter in solar energy application, while this parameter is directly related to the performance of solar thermal and photovoltaic systems. The present research work mainly focused on the implementation of ANN technique to predict Operational Performance of the SWH System Using ANN Approach. A distinctive method is used to predict how well the solar-powered water heater in Bhopal City will function. This is done by combining GSR as well as SWH ANN models. The output of GSR from the GSR-ANN simulation of Bhopal city is used as a parameter for input in the combination ANN model for the solar-powered water heating system. The output that was obtained is compared to the values that were tested. The error study showed that the mixed ANN model that was created is the best option for predicting SWH performance, as it has the lowest RMSE and MAPE along with the highest R.